Model bimbingan dan konseling menggunakan cinematherapy untuk mereduksi keyakinan negatif - Nikmarijal Nikmarijal; Cece Rakhmat; Ahman Ahman; Nandang Rusmana; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Negative beliefs cause many problems in living life so that it can prevent oneself from developing healthy self-esteem, prevent oneself from feeling fulfilled in life, prevent individuals from developing healthy relationships. Negative beliefs can limit what is seen and lead to actions against the best interests of our loved ones and ourselves. Guidance and Counseling Using Cinematherapy can be used to reduce these negative beliefs. Cinematherapy is defined as an umbrella term for a therapeutic process that involves the assignment of films to clients in order to promote and enhance therapeutic benefits. This study uses a single case experimental designs using the A-B-A design with one subject. From the hypothesis test, the result of the Asmyp probability number is obtained. Sig.(2-tailed) is 0.068, or the probability is above alpha 0.05 (0.001 < 0.05). From these results, Ho is rejected and H1 is accepted. From the results of the research conducted, it can be concluded that cinematherapy is effectively used to reduce negative beliefs